Electrical conductivity of pectin‑based biopolymer electrolytes: search for a theoretical framework - Kumar, Kailash; Mohd Noor, Ikhwan Syafiq; Pandey, Shri Prakash; Bhattacharya, Bhaskar; Saxena, Amit (Springer Science and Business Media Deutschland GmbH, 2024)
This paper reports the successful fabrications of polymer electrolytes using biopolymer pectin in conjunction with ammonium azide (NaN3) salt by solution casting method. The ionic conductivity of these electrolytes was evaluated using EIS at room temperature. Among the compositions tested, the highest conductivity of 2.3×10−3 S cm−1 was observed to sample of 5 wt.% of NaN3. The charge carriers' concentration (n) and mobility (μ) were calculated to understand the conductivity behavior attributed to dispersoids. For the calculation of n and μ, two theoretical models were used, namely the Trukhan and the S&G Model. The correlations between conductivity, n and μ are discussed.